Orientaciones para la enseñanza de la escritura en la educación inicial y primaria en discursos oficiales y científicos. Colombia, 1994-2004 - Borja Alarcón, Isabel; López Vega, Alfonso; Méndez Rivera, Pilar Esther; Segura Escobar, Aldemar; Rincón, Flor Ángel (Revista Científica, 2007)
This article provides a synthesis or overview of the research project entitled, "Approaches to the teaching of writing at foundation and primary level in official and scientific discourses, Colombia 1994 2004". It is composed of an introduction, which provides a general overview of the aforementioned paper, then, within the "Development" section, there are 3 subsections: 1) A section which examines the major recognised theories of the writing teaching, 2) A section which considers the theories which have been highlighted in official discourses; 3) and a section which introduces approaches of the scientific discourse to the teaching of writing. At the same time, the paper includes the conclusions contained in the research paper and the bibliography of this article.